Knowledge on Reproductive Health Status: Study of Sunkoshi Rural Municipality, Sindhuli District - Dahal, Ramchandra (GS WOW: Wisdom of Worthy Research Journal, 2025)
Reproductive health (RH) is essential for overall human development, yet rural populations in Nepal, including Sunkoshi Rural Municipality, face challenges in RH knowledge, service utilization, and male involvement. This study examines reproductive health knowledge and male participation in RH practices among ever-married women aged 15–49 in Ward No. 4 of Sunkoshi Rural Municipality. A descriptive and analytical research design was employed, collecting primary data through structured household and individual questionnaires from 160 respondents. Findings show that 88% of women accessed antenatal care (ANC), but only 25% completed the recommended four visits. Husbands played a key advisory role during pregnancy (36.8%), yet only 42.1% of women perceived their husbands as emotionally supportive during childbirth. Cultural norms, household responsibilities, and lack of awareness limited male involvement and consistent use of RH services. Significant knowledge gaps and infrastructural challenges persist in rural Nepal. The study underscores the need for gender-inclusive, community-based RH interventions that empower women and actively engage men. Strengthening healthcare infrastructure and addressing socio-cultural barriers are critical to improving maternal health outcomes and advancing public health goals in rural settings.